Talent Development Models and Leadership Decision Ethics in Facing Business Disruption in East Java Regional-Owned Enterprises - Ferra Eka Ramadhani; Harry Purnomo Salim (JOURNAL KOPERASI DAN MANAJEMEN, 2026)
Purpose – This study aims to examine the relationship between structured talent development, ethical leadership decision-making, and organizational resilience in Regional-Owned Enterprises (ROEs) in East Java, Indonesia. It specifically investigates whether ethical leadership mediates the relationship between talent development and organizational resilience in responding to business disruption. Design/methodology/approach – This study employed a quantitative research design. Data were collected through structured surveys from 250 mid-to-senior-level managers working across various ROEs in East Java. Structural Equation Modeling (SEM) was employed to examine the hypothesized relationships among talent development, ethical leadership, and organizational resilience. Findings – The results indicate that comprehensive talent development significantly enhances ethical leadership decision-making (? = 0.67, p < 0.001). Furthermore, talent development and ethical leadership have significant positive effects on organizational resilience, with coefficients of ? = 0.52 and ? = 0.48, respectively (p < 0.001). Ethical leadership also significantly mediates the relationship between talent development and organizational resilience. These findings demonstrate that systematic talent development contributes to organizational resilience both directly and indirectly by strengthening ethical leadership capabilities. Research limitations/implications – This study is limited to mid-to-senior-level managers in Regional-Owned Enterprises in East Java, which may limit the generalizability of the findings to other regions, organizational levels, or sectors. The quantitative and cross-sectional design also limits the ability to capture changes in organizational resilience over time. Future research could employ longitudinal approaches and examine additional factors such as organizational culture, digital capability, innovation capability, or strategic agility. Originality/value – This study contributes to human resource development and leadership literature by integrating talent development, ethical leadership, and organizational resilience within a single explanatory framework. Its originality lies in demonstrating the mediating role of ethical leadership in translating talent development into greater organizational resilience. The study also provides empirical evidence from Regional-Owned Enterprises in East Java, representing an underexplored developing-economy context.